Spatial Distribution Patterns of Urban Growth, Dasymetric Mapping, and Air Pollution Standard Index (ISPU) in Bogor Regency (2018-2023) - Ramadhan, Alfarisi; Hermawan, Erwin; Hudjimartsu, Sahid Agustian (Politeknik Negeri Batam, 2025)
Bogor Regency has undergone rapid industrialization and urban growth, raising concerns about deteriorating air quality and its health impacts. This study aims to analyze the spatial distribution of urban expansion and its relationship with air pollution levels between 2018 and 2023. Using Sentinel-5P and Sentinel-2A satellite imagery processed via Google Earth Engine (GEE), the research maps changes in land use and monitors key pollutants such as nitrogen dioxide (NO₂) and sulfur dioxide (SO₂). The Air Pollution Standard Index (ISPU) is used to classify air quality conditions. The results indicate a notable increase (16%) in urban areas, with population density rising from 178 to 180 inhabitants per hectare, and a shift toward higher pollution categories, with significant portions of the region now classified as